The Ice cover of the Greenland Sea.: An Evaluation of Oceanographic and Meteorological causes for year-to-year Variations. - Skov, Niels Aage (Meddelelser om Grønland, 1970)
A criterion is defined to compare seasonal ice coverage in the Greenland Sea for the years 1900-57, and the areal coverage is graphed using the 1898-1913 average as a standard. The factors yielding possible influence on short-term variations of the ice cover are examined individually and their relative importance established. The influence of ocean currents is evaluated by analysis of hydrosections across the East Greenland Current at 74°-76 °N and across the North Atlantic Current in the Faeroe-Shetland channel. Data from the latter area are used for numerical analysis of heat imported to the Greenland Sea by the North Atlantic Current in the 1927-52 period. Details about the Irminger Current’s behavior are derived from station data from Denmark Strait and from surface temperatures at Selvogsbanki south of Iceland. Year-to-year variations are found to exist in the flow volumes of all three currents, and correlations with seasonal ice coverage in the Greenland Sea are shown. Above-average precipitation in conjunction with below-average storm activity is found to have negligible influence on the ice regime, and no significant correlation is found. The possible effect of evaporation is computed to be far below the threshold of detectability. Air temperatures in the Norwegian-Greenland Sea region display a trend of increase throughout the period studied, in harmony with a concurrent trend of decreasing ice cover; but no causal relationship is in evidence. The effects of strengths and directions of predominant winds are examined, and good correlations are shown between ice cover flu ctuations and easterly wind components at Norwegian coastal stations. At the points of major currents’ entrances to and exits from the Greenland Sea the wind effects are complex and cannot be fully evaluated on the basis of existing data. The fluctuations of ocean currents entering and leaving the Greenland Sea and of water movements within the Greenland Sea remain as the apparent determinant of year-to-year variations of the ice cover.